2015
DOI: 10.1021/acs.estlett.5b00130
|View full text |Cite
|
Sign up to set email alerts
|

A Fluence-Based Method for the Direct Comparison of Photolysis Kinetics under Variable Light Regimes

Abstract: Chemical actinometers are traditionally used to account for photochemical experiments conducted under different light regimes (simulated vs natural; also seasonal, daytime, cloud cover, and latitude changes). Their many limitations and the lack of a universally applicable actinometer demand development of a new approach for studying environmentally relevant photochemical processes in sunlight. We suggest the use of fluence-based rate constants (converted to time-based rate constants and half-lives with irradia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…In practice, the stringency of these requirements depends on how accurately the spectral distribution of the radiation is quantified and the available equipment. For example, identical time scales are unnecessary if radiometric monitoring and correction can be calibrated to actinometer reaction rates . Nonetheless, actinometry is most reliable when it meets the stated conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In practice, the stringency of these requirements depends on how accurately the spectral distribution of the radiation is quantified and the available equipment. For example, identical time scales are unnecessary if radiometric monitoring and correction can be calibrated to actinometer reaction rates . Nonetheless, actinometry is most reliable when it meets the stated conditions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, identical time scales are unnecessary if radiometric monitoring and correction can be calibrated to actinometer reaction rates. 7 Nonetheless, actinometry is most reliable when it meets the stated conditions. Dulin and Mill introduced two actinometers based on photonucleophilic substitution of excited state nitrobenzene derivatives by pyridine.…”
Section: ■ Introductionmentioning
confidence: 99%
“…5 The half-life time of 2-hydroxy-4methoxybenzophenone-5-sulfonic acid (BP4) was approximately 15 days under constant irradiation equivalent to noon midsummer sunlight. 6 The bare BP backbone without the adjacent hydroxyl group and the intramolecular hydrogen bond, however, is incapable of releasing the light energy in the form of heat to return to its low-energy state after excitation under UV irradiation. Instead, it tends to transfer the extra energy to other molecules, such as dissolved oxygen and other organic compounds in water.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that 2-hydroxy-4-methoxybenzophenone (BP3) was only degraded by 4% after continuous irradiation for 4 weeks in aqueous solution . The half-life time of 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid (BP4) was approximately 15 days under constant irradiation equivalent to noon midsummer sunlight …”
Section: Introductionmentioning
confidence: 99%